Análise de estratégias de fim de vida para placas de circuito impresso: uma abordagem baseada em avaliação do ciclo de vida - Silva, Abner Fernandes Souza da (Universidade Federal de São Carlos, 2025)
Printed Circuit Boards (PCBs) are important components of electrical and electronic equipment. Due to their composition, which includes materials of high value as well as others with potential hazards to the environment and human health, they have become the focus of growing concern. The present work analyzed strategies for end-of-life management of printed circuit boards (PCBs) in Brazil, integrating a systematic literature review, modeling for the prediction of waste electrical and electronic equipment (WEEE), and scenario assessment using Life Cycle Assessment (LCA). The significant increase in publications addressing hydrometallurgical methods for metal recovery from PCBs has highlighted the potential for sending them to recycling processes. However, gaps such as recovery processes through biometallurgy and the management of reverse logistics still need to be explored, pointing to opportunities for future research. Forecasting WEEE generation in Latin America proved to be essential, where per capita GDP and Human Development Index (HDI) were used as variables. The generated model showed that economic and social development directly impact the quantity of waste generated, reinforcing the importance of specific public policies for the management of WEEE reverse logistics. The possible end-of-life scenarios for PCBs were evaluated using the LCA technique, and the results indicated that a recycling plant in Brazil, based on the acidic hydrometallurgical method, would be the most sustainable solution among the scenarios evaluated. The recovery of precious metals, such as gold and palladium, proved to be fundamental for reducing environmental impacts and generating economic value by reinserting materials into the production cycle, while processing in Brazil minimizes the impacts associated with transport to other countries, as currently occurs. This work contributes to the advancement of sustainable management of reverse logistics of electronic waste by providing well-founded support for public policies and business initiatives, reinforcing the importance of regional strategies and investments in innovative technologies to promote a circular economy.
Life cycle assessment-based analysis of end-of-life strategies for printed circuit boards
Keywords: Avaliação do Ciclo de Vida; Logística Reversa; Placas de Circuito Impresso; Economia Circular; Resíduos de Equipamentos Eletroeletrônicos; Life Cycle Assessment; Reverse Logistics; Printed Circuit Board; Waste Electrical and Electronic Equipment; Circular Economy; ENGENHARIAS::ENGENHARIA DE PRODUCAO::GERENCIA DE PRODUCAO; 12. Consumo e Produção Responsáveis; 9. Indústria, Inovação e Infraestrutura; 11. Cidades e Comunidades Sustentáveis; 13. Ação contra a Mudança Global do Clima